2021
DOI: 10.3390/molecules27010108
|View full text |Cite
|
Sign up to set email alerts
|

Recent Studies on Berry Bioactives and Their Health-Promoting Roles

Abstract: Along with the increased knowledge about the positive health effects of food bioactives, the eating habits of many individuals have changed to obtain higher nutritional benefits from foods. Fruits are among the most preferred food materials in this regard. In particular, berry fruits are important sources in the diet in terms of their high nutritional content including vitamins, minerals, and phenolic compounds. Berry fruits have remedial effects on several diseases and these health-promoting impacts are assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 177 publications
(206 reference statements)
0
3
0
Order By: Relevance
“…Because of this, calcium requirements are higher during adolescence. Calcium is also very important during later adulthood, which has significant consequences from a public health perspective because an inadequate intake of calcium may increase the risk of osteoporosis [38].…”
Section: Comparison Of Raspberry Seed Characteristics Before and Afte...mentioning
confidence: 99%
“…Because of this, calcium requirements are higher during adolescence. Calcium is also very important during later adulthood, which has significant consequences from a public health perspective because an inadequate intake of calcium may increase the risk of osteoporosis [38].…”
Section: Comparison Of Raspberry Seed Characteristics Before and Afte...mentioning
confidence: 99%
“…In recent years, research regarding natural sources of bioactive compounds (BACs) with potential health benefits has attracted considerable attention in the field of food science and nutrition. Among these sources, berries and medicinal plants have emerged as promising reservoirs of BACs [1], with a variety of properties that contribute to human health and well-being [2]. In this context, strawberry (Fragaria ananassa × Duch.)…”
Section: Introductionmentioning
confidence: 99%
“…Anthocyanins, water-soluble pigments, are classified into the polyphenolic flavanol family composed of anthocyanidin aglycone and one or more glycosides [ 1 , 2 ]. To date, more than 700 anthocyanins have been identified in various plants, including berries, and are reported to have diverse pharmacological properties, such as anti-inflammatory, antidiabetic, antithrombotic and antiallergic effects [ 3 - 5 ]. In particular, accumulating studies have shown that the improvement of aging-related chronic diseases such as neurodegenerative, cardiovascular, and ocular diseases by anthocyanins is closely associated with their potent antioxidant action [ 3 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%